Biomedical, psychological, environmental and behavioural factors associated with adult obesity in a nationally representative sample. (25th February 2019) - Cheng, Helen; Montgomery, Scott; Green, Andy; Furnham, Adrian
Abstract: Objective: To identify personality, biomedical and behavioural factors associated with adult obesity in a large longitudinal sample. Method: In total, 5360 participants with data on personality, neurological functioning, maternal smoking during pregnancy, education and occupation, physical exercise, adult self-reported BMI and obesity were included in the study. Obesity at 55 years was the outcome variable. Results: The rates of obesity increased from 9.5 to 22.8% from age 33 to 55 years. Logistic regression analyses (adjusted estimates) showed that childhood neurological functioning (OR = 1.32: 1.07–1.63, P < 0.01), maternal smoking during pregnancy (OR = 1.42: 1.22–1.65, P < 0.001), educational qualifications (OR = 0.54: 0.37–0.79, P < 0.01), trait conscientiousness (OR = 0.80:0.74–0.86, P < 0.001) and physical exercise (OR = 0.87: 0.82–0.92, P < 0.001) were significant predictors of obesity at age 55 years for both men and women. Trait extraversion for men (OR = 1.16: 1.07–1.26, P < 0.001) and trait emotional stability for women (OR = 0.90: 0.82–0.99, P < 0.05) were also significant predictors of the outcome variable. Conclusion: Biomedical, psychological, environmental and behavioural factors were all associated with adult obesity.